HUBUNGAN PROGRAM MAKAN BERGIZI GRATIS (MBG) DENGAN TINGKAT KEHADIRAN SISWA KELAS V SEKOLAH DASAR - Paulus Rivaldi Pili Ngoba; Jesica Nenabu; Maria Aprilia Meli Maing; Gabriela Solsido Ametuke; Adam Bol Nifu Benu; Habibi Musa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The Free Nutritious Meal Program (MBG) is a government priority policy aimed at improving children's nutritional status, promoting learning readiness, and supporting equitable distribution of educational quality. Adequate nutrition is closely related to students' cognitive development, stamina, and learning resilience, thus influencing their school attendance. This study aimed to determine the relationship between the implementation of the MBG Program and the attendance of fifth-grade elementary school students. The study used a quantitative, descriptive correlational approach, with a sample of 28 fifth-grade students, drawn using a saturated sampling technique. The instruments used were a 3-point Likert scale questionnaire and student attendance data documentation. The descriptive analysis showed an average score of 1.86 for students' perceptions of MBG, which falls into the